2021
DOI: 10.7717/peerj.11251
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA taurine upregulated gene 1 is downregulated in osteoporosis and influences the osteogenic differentiation of bone marrow mesenchymal stem cells

Abstract: Background With aging, an imbalance in bone remodeling leading to increased bone resorption and decreased bone formation is thought to contribute to osteoporosis. Osteoblastic differentiation of bone marrow mesenchymal stem cells (BMMSCs) plays a vital role in the pathogenesis of osteoporosis. However, the detailed molecular mechanisms of osteoporosis remain incompletely understood. Given that long non-coding RNA taurine upregulated gene 1 (lnc TUG1) plays a critical role in the osteogenic diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In addition, recent studies have demonstrated the important role of TUG1 in osteogenic differentiation. For insurance, Teng et al found that the TUG1 was downregulated in osteoporosis and affected the osteogenesis of BMSCs [9]. TUG1 also promoted osteoblast differentiation by sponging miR-204-5p [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies have demonstrated the important role of TUG1 in osteogenic differentiation. For insurance, Teng et al found that the TUG1 was downregulated in osteoporosis and affected the osteogenesis of BMSCs [9]. TUG1 also promoted osteoblast differentiation by sponging miR-204-5p [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, emerging evidence suggested that TUG1 was crucial to osteogenic lineage commitment of several mesenchymal stem cells (MSCs) [9][10][11]. TUG1 expression levels are downregulated in patients with osteoporosis, suggesting possible involvement in osteogenesis [9]. Another study revealed that TUG1 functioned as a positive regulator in osteogenic differentiation of BMSCs through the AMPK/mTOR/autophagy pathway [11].…”
Section: Introductionmentioning
confidence: 99%
“…RUNX2 is the earliest and most specific marker gene in the process of bone formation. RUNX2 also serves as a marker for osteoblasts differentiation [ 29 ]. The RUNX2 homozygous knockout mice correlated with rib aplasia [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research demonstrated that lncRNA TUG1 accelerates the osteoblasts differentiation by sponging miR-545-3p and increasing CNR2 expression [ 41 ]. Teng, Z., et al [ 42 ] verified lncRNA TUG1/miR-23b/Runx2 signaling prompt the osteogenic differentiation of BMSCs, it might provide a new insight for the diagnostic and therapeutic strategies for osteoporosis. Moreover, lncRNA TUG1 also down-regulated bFGF protein expression for the osteogenic capacity of TSPCs by promoting bFGF ubiquitination [ 43 ].…”
Section: The Research Status Of Lncrnas Related To Osteogenic Differe...mentioning
confidence: 99%